Membangun Budaya Organisasi yang Positif untuk Mendukung Kinerja Pendidik dan Tenaga Kependidikan - Dina Dwi Juliawati; Putri Adelia Anastasyiah; Agustin Hanivia Cindy; Windasari, Windasari (Yayasan Literasi Sains Indonesia, 2024)
It's interesting to do research on organizational culture because it relates to the unique characteristics that distinguish one organization from the other. One of the things that distinguishes an organization from another is the system of meaning adopted by all its members. Therefore, organizational culture must help the growth of the organization, especially by increasing the retention of employees, both individuals and teams. Organizational development is crucial because without it, the company cannot function. In order for the results to be profitable, appropriate improvements must continue to be made and incorporated into the current organizational culture. A culture within an organization can influence change and be a driving factor in its growth. Finding out how important organizational culture is in building healthy organizations is the goal of this writing through a comprehensive literature review. The method used is to conduct a systematic study of various related literary sources, such as scientific journals, books, and previous research reports. New strategies for organizational development are needed to obtain more complete and valid data on how organizational culture correlates with organizational growth. The results of the literature survey show that a positive organizational culture, characterized by values such as mutual respect, collaboration, trust, and openness, has a significant impact on the performance of teachers and educators. This positive culture increases motivation, job satisfaction, and encourages sustainable professional development.